Convergence of Vortex Methods for 3-D Euler Equations (Journal of Computational Mathematics, 2000)
In this paper we apply an approach introduced in [6] [7], where continuous norms and high order estimates and extension are used, to study the convergence of vortex methods for the 3-D Euler equations in bounded domains as the initial vorticity $w_0$ and the curl of the body force $f$ are non-compactly supported functions. Convergence results are proved.
Keywords: Euler equations; Vortex methods; Convergence; Initial-boundary value problem.